Crisis averted : the hidden science of fighting outbreaks - Rivers, Caitlin (Viking, 2024)
"A fascinating window into the secret life of epidemiology, weaving together stories of triumph and tragedy, with a boots-on-the-ground perspective on how we can avert the next public health crisis There are few visible markers of the accomplishments of public health. If epidemiologists do their jobs, nothing happens. An outbreak does not grow into an epidemic. A child does not go hungry. A would-be smoker never lights up. These achievements are rarely noticed or celebrated, but Caitlin Rivers lives for such victories. By making sure that things don't happen, she and legions of scientists, practitioners, and policymakers change the course of history. We have many of the tools and experiences needed to prevent the next crisis, but countless challenges remain, including constantly emerging pathogens, the rapid growth of biotechnology, and the inconsistent cycles of funding for government organizations like the CDC. Progress can be slow, even with the next pandemic potentially right around the corner, but the unsung heroes in public health remain focused on their missions. Crisis Averted is their story-from the eradication of smallpox in the 20th century to today's safeguards against extraterrestrial germs. By taking a candid look at how we solve problems in public health, Caitlin Rivers illuminates the role of epidemiology in all our lives and lays out the case for what can be accomplished, given sufficient vision, leadership, and resources. Crisis Averted is an inspiring and galvanizing clarion call for us to work together towards a healthier, more resilient future"--